Reformas necesarias a la ley contra la violencia de la mujer y familia, en cuanto a la prescripción de la acción, por actos de violencia intrafamiliar - Idrovo Cabrera, Pablo (2016)
The matter as is necessary to the Law Against Violence Against Women and Family Reforms, as to the statute of limitations for acts of domestic violence has been one of the major concerns me that has emerged due to large number of cases that have been initiated in the Courts, and have failed to have adequate resolution given that have been abandoned and therefore declared the prescription by the authority, by the Judges of domestic violence as a mechanism to debug the red tape of causes in the unit where the process began. To be the responsibility of the State to ensure the rights of vulnerable groups, it is up to it, through the judicial officers to ensure compliance with the rights enshrined in the Constitution and the law, so it has the absolute duty to require the principles of speed in the prosecution of infringements and the principle of immediacy are met fully, so that the acts of violence perpetrated within the family does not go unpunished and what's more, through the diligent performance of the responsible for the administration of justice is eradicated violence as a generating element of the nuclear family unit, towards a more united and consolidated company, and reflects the stability of households in society Ecuador, and thus strive to meet each and every one of the legal commitments that the State assumed by the Constitution, international treaties and Current Legislation. 7 We cannot forget that the Ecuadorian State, pursuant to Article 36 of the Constitution of the Republic of Ecuador protects and guarantees to groups that are located in high vulnerability, especially women, children and adolescents so that when defiled their rights these are prone to violation of their human rights, and also subject to discrimination, which prevents the enjoyment of those rights on an equal basis. Violence against Women and the Family in our country should be considered as a violation of human rights, to be consistent with the resolution from the "World Conference on Human Rights held in Vienna in 1993" and that clearly explains the Declaration and Plan of Action, but prior to that in the year 1979, the General Assembly of the United Nations adopted the Convention on the Elimination of All forms of Discrimination against Women (CEDAW) and it is considered violence as a violation of human rights, and to be the state of this subscriber agreement is required to apply this principle, as established in Article 426 of the Constitution of Republic of Ecuador, which reads: Art 426. Everyone, authorities and institutions are subject to the Constitution. The judges, administrative authorities and public servants directly apply constitutional norms and under international human rights instruments if they are more favorable than those established in the Constitution, although the parties do not expressly invoke. The rights enshrined in the Constitution and international human rights instruments will immediately compliance and enforcement. It may be invoked lawlessness or disregard for the rules to justify the infringement of the rights and guarantees established in the Constitution to dismiss the action filed in his defense, nor to deny recognition of such rights. The fight against violence and abuse directed especially to children and adolescents is recognized as a subsidiary obligation of the State and its agents, through the International Convention on the Rights of the Child (and girl) from 1989. The Ecuador to ratify the Convention Belem Do Para, exhaustively recognizes that the rights of women and girls, universal human rights are enshrined and is committed to promote and protect the full enjoyment of these rights. This was later reiterated by incorporating the Inter (Belem do Para) in the existing legal order as Act 103 Violence against Women and the Family. These instruments recognize the fundamental right to a life free of violence, among which are the right to life , respect for the physical, mental and moral integrity, liberty and security of person, not to be subjected to torture , abuse inhuman and degrading , to equality before the law, which is why the admissibility of the shares of domestic violence must be overcome at the time that the action is properly sanctioned as a unique mechanism to refocus the Company and the achievement of a household free of violence to ensure equality between women and men as an obligation incumbent on the State, and when the public official and state agents violate the right to equality are violating this responsibility. Hence breaches of domestic violence should be barred.